The classification of users processes and their impact on care in emergency rooms in hospitals - Consuelo Cubero Alpízar; Kattia Medina Arias (Universidad de Costa Rica, 2013)
This article is a preview of the research entitled "Strategies for addressing and classification of users in emergency departments in hospitals" which generally aims to "assess strategies for user attention in hospital emergency departments" and develops in the form of evidence-based nursing. The same refers to the implementation of different strategies for classifying users (as) in the Hospital Emergency Services (ED) by the nursing staff. Methodology was implemented based nursing practice in the Evidence (PEBE) which consists of the following steps: formulation of questions that can be answered; comprehensive literature search, critical reading of the documents obtained, applying the most appropriate intervention, and evaluation of the intervention Among the main results is that in terms of staging modalities are varied from structured easily replicated by randomly attention to arrival, the research shows that structured care becomes an essential tool for professionals nurse, since they become training together with the building blocks for user classification by these professionals.